Schwerbehinderung und Mobilitätseinschränkung. Von der Notwendigkeit des "Designs für alle". - Becker, Josef; Schubert, Susanne; Vollmer, Peter E.; Wahlster, Michael W. (Deutscher Verkehrs-Verl., 2007)
Ein großer Teil der Bevölkerung ist schwerbehindert beziehungsweise mobilitätseingeschränkt. Er stellt für Verkehrsverbünde und Verkehrsunternehmen ein beachtliches Kundenpotenzial dar, das oft verkannt wird. Der Artikel stellt diese Gruppe vor. difu

Over the last few years, regional transport and individual transport carriers have increasingly focused their attention on handicapped persons and on those affected by restricted mobility. This group of people assumes strategic importance on account of its size and a revised legal framework. Almost every person may, in the course of his/her life, be affected by forms of limited mobility. This may result from physical handicaps, being accompanied by a pram, luggage or bicycle in public means of transport, by temporary restrictions (e.g. accidents) plus more frequent age-related impediments such as walking, vision and hearing. Especially the older age group is going to witness notable expansion, thus creating a potentially large and growing market that has not yet been tapped in any optimal way. More customers could be secured and more revenue could be generated on condition that all means of public transport, which meet users' needs, offer more information about their inherent usefulness overall. difu
Keywords: Öffentlicher Verkehr; Behinderter; Kranker Mensch; Alter Mensch; Mobilität; Verkehrsunternehmen; ÖPNV; Schwerbehinderter; Barrierefreiheit; Kundenorientierung